C-C and C-H bond cleavage reactions in the chrysene and perylene aromatic molecules: An ab-initio density functional theory study - Shanshal, Muthana Abduljabbar; Yusuf, Qhatan Adnan (European Journal of Chemistry, 2017)
The ab-initio DFT (B3LYP) method is applied for the study of C-C and C-H bond cleavage reactions in chrysene and perylene aromatic molecules. It is found that, the C-C bond cleavage proceeds via a singlet aromatic transition state, compelled through a disrotatoric ring opening reaction. A suprafacial H atom shift follows the transition state in some of these reactions, where the formation of a methylene -CH2,acetylenyl-, allenyl- or butadienyl- moiety in the final product is possible. Activation energies are calculated for the ring opening and show the following values; for chrysene, 136.97-197.69 kcal/mol and for perylene, 160.87-187.33 kcal/mol. The reaction energies range from 95.57-162.42 kcal/mol for chrysene and 98.12-168.28 kcal/mol for perylene. The calculated cleavage reaction energies for all C-H bonds in both molecules are almost similar, 116-117 kcal/mol. Their activation energies however are different, for chrysene they range from 148.57-154.97 kcal/mol and for perylene 148.30-162.73 kcal/mol.